Closed for the season - Hahn, Mary Downing (Boston : Sandpiper/Houghton Mifflin Harcourt, 2009)
When thirteen-year-old Logan and his family move into a run-down old house in rural Virginia, he discovers that a woman was murdered there and becomes involved with his neighbor Arthur in a dangerous investigation to try to uncover the killer.
School Library Journal, September 2009.
Horn Book, October 2009.
Voice of Youth Advocates (V.O.Y.A.), October 2009.
Kirkus Review, May 2009.
Library Media Connection, October 2009.
School Library Journal.
Keywords: Murder -- Juvenile fiction; Neighbors -- Juvenile fiction; Friendship -- Juvenile fiction; Murder -- Fiction; Neighbors -- Fiction; Friendship -- Fiction; Mystery and detective stories; Homicide -- Fiction; Neighbors -- Fiction; Friendship -- Fiction; Mystery fiction; Murder -- Fiction; Neighbors -- Fiction; Friendship -- Fiction; Mystery and detective stories; Virginia -- Juvenile fiction; Virginia -- Fiction; Virginia -- Fiction; Virginia -- Fiction; Mystery fiction